Uso de guías didácticas en el Taller de Primeros Auxilios para Enfermería. - Derby Muñoz Rojas (Universidad de Costa Rica, 2011)
This study aimed to determine the feasibility of using tutorials on course work: EE-0220 Taller de Primeros Auxilios from the nursing program at the University of Costa Rica, which were implemented during the second cycle school in 2008. Purpose: The investigation determined the perception of the students on the usefulness of the ?Guías Didácticas? as a tool to facilitate the process of learning of first aid. Methodology: Was an educational research, type of classroom action research. Instruments and techniques: to collect the information used a brainstorming and a questionnaire a population to 18 students. Result: the study can conclude that it was found advantageous to use the guides as they contributed to the assimilation of the contents by the students. In conclusion it is said that successful teaching strategies used allow the students use their participation in the teaching-learning process.